Traditional and Computer-Based Assessment of Executive Functions - Željka Nikolašević; Bojana M. Dinić; Milan Oljača; Ilija Milovanović; Jasmina Kodžopeljić; Vojislava Bugarski Ignjatović (Primenjena Psihologija)
This study aimed to assess the psychometric properties of two newly developed computer-based tasks (i.e., Mental Shifting/Flexibility Task and Auditory-Visual Go/No-Go Task) for measuring two key domains of executive functions (EF) - inhibition and mental shifting (flexibility) - in healthy adults. Together with these tasks, traditional paper-and-pencil tests were used for assessing construct validity (Wisconsin Card Sorting Test - WCST, Trail Making Test - TMT, Verbal Fluency Tests, and Advanced Progressive Matrices- APM). The sample consisted of 468 adult twins (70.7% female, mean age 24.06 years) or 234 twin pairs. Results revealed low to moderate correlations between the reaction times and the number of errors in the computer-based tasks and traditional tests. Specifically, the Mental Shifting/Flexibility Task showed significant correlations with the TMT and the WCST. The Auditory-Visual Go/No-Go Task was significantly related to TMT and APM, suggesting shared cognitive processes linked to inhibition, cognitive flexibility, and processing speed. The computer-based tasks demonstrated moderate to good ICC reliability, especially in reaction time measures, while error rates showed poorer reliability. It was concluded that computer-based tasks are useful for measuring executive functions. However, further validation, development of standardized norms, and optimization of these tools are needed. Future research should explore how these tools can be integrated into existing cognitive assessment batteries for more accurate measurement of executive functions across diverse populations and clinical contexts.